Isolation, Antibiogram and Molecular Characterization of Escherichia coli in Broiler Flocks - Choudhari, Pradhnya; Ghodasara, Dinesh J.; Kabariya, Digjay V.; Bhanderi, Bharat B.; Momin, Sohilabbas G. (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
The present study was conducted on 30 broiler flocks (organs of 5 birds per flock homogenized as composite or pooled one sample) for  cultural isolation, identification, biochemical characterization and antibiogram profile of Escherichia coli (E. coli). All the 30 composite  samples (100%) revealed colonies with typical morphology and biochemical characteristics of E. coli. Antibiogram study was conducted  by disc diffusion method and results revealed the highest 100% sensitivity to antibiotic colistin followed by amikacin (83.33%) ceftriaxone  (80.00%), chloramphenicol (60.00%), cefotaxime (60.00%) gentamicin (53.33%) and norfloxacin (6.66%), while the organisms were  highly resistant to norfloxacin (83.33%) followed by gentamicin (46.66%). In addition, all the 30 E. coli isolates were tested for presence  of virulence associated genes, i.e., iss, papC, tsh and vat by PCR using gene specific primers. Result showed the highest prevalence of iss gene 26/30 (86.66%) followed by vat 24/30 (80.00%), tsh 16/30 (53.33%) and papC 9/30 (30.00%) in the flocks tested.
Keywords: Escherichia coli; Prevalence; Antibiogram; Broiler; Virulence genes